A imunidade de contribuições para seguridade social das entidades beneficentes de assistência social - Haik, Cristiane Fátima Grano (2011)
The scope of this work is to study the immunity of social contributions for the social security of charitable entities for social assistance, as granted by article 195, paragraph 7 of the Federal Constitution. For this purpose, we shall start with a historical summary and introductory notions regarding the non-tax obligations as well as the social assistance, inserting it in the area of welfare, along with health and social security. We shall also deal with the doctrine of the non-tax obligations immunity, exemption and non-levy -, and more precisely, of the immunity on contributions for the social security of the charitable entities of social assistance, also addressing the two major school of thoughts leading the discussions on this subject, in other words, if the capable legal instrument to regulate the requirements for the enjoyment of the immunity set forth in paragraph 7 of article 195 of the Federal Constitution is a supplementary law, in this case, the National Tax Code, or an ordinary law, such as Law number 12.101 of 2009. Thus, we shall propose a more teleological than legal analysis of the subject, aiming at achieving the path that gives more constitutional effectiveness. We adopted the deductive method on the research, which is built from a reasoning developed on an incrementally basis. In other words, starting with the most general aspects that the matter comprises, then going to the most specific one. The instruments that we used for the development of such method were (i) bibliographic research pertaining to the matter under analysis (ii) historical evolution, as well as (iii) applicable laws and (iv) case laws issued by the Federal Supreme Court, as an instrument of corroboration, when applicable